CRITERIAL EVALUATION OF MEASURES FOR THE TRAFFIC ORGANIZATION - Lobashov, O. O.; Burko, D. L. (Science and Transport Progress, 2008)
The issues of evaluation of activities upon the organization of traffic at the transport city network are being studied. The activities as to their social, ecological and economical efficiency rates are brought up to estimate.